How trait mindfulness protects late adolescents from stress-induced sleep problems: the unique role of mindfulness facets and gender differences - Huiting Cao; Jing Qian; Fenghua Tang; Yunyan Dong; Haining Ren; Xiaoran Xue; Ningning Mao; Xiaoyu Liu (BMC Psychiatry)
Abstract Background Understanding sleep problems in late adolescents caused by daily stress is essential due to their increased vulnerability to stress-related sleep issues. While previous research has demonstrated the potential protective effect of trait mindfulness, facets of mindfulness were found to have unique functions against the negative impact of stress, and the unique impact of each facet of mindfulness on the sleep problems caused by the negative impact of stress remains unclear. Thus, this longitudinal study aimed to assess the impact of stressful life events on sleep problems a year later among late adolescents and to explore the moderating effects of the five trait mindfulness facets. Gender differences have been observed in mindfulness’s protective effects, yet how gender influences each mindfulness facet remains unclear. This study also examines how gender moderates the effects of individual mindfulness facets. Methods The study tracked 1,926 Chinese vocational high school students (M age = 18.49) over a year, assessing them for their sleep problems, perceived impact of stressful life events, and mindfulness facets through self-reported questionnaires. Multivariate analysis was used to investigate the moderating effects of each mindfulness facet on the relationship between stressful life events and sleep problems one year later. Then, gender differences were examined through multi-group comparison. Results A higher impact from stressful life events predicted more sleep problems a year later. Notably, among all five facets of mindfulness, only Observing significantly buffered the negative impact of stressful life events on sleep problems, in females but not in males, thus gender moderated the impact of Observing. Conclusions This study suggested that Observing uniquely protected young females from the negative impact of stressful life events on their sleep problems a year later. Since the measurement tool for the Observing facet only had 1 question tested on observing inner feelings, and other questions are all about observing bodily sensations and outer environments, this study implies that insomnia therapies focus on enhancing the ability to anchor attention in the present moment, especially towards bodily sensations and the outer environment, may be particularly effective in buffering the long-term impact of daily stressors on sleep for young females. Trial registration Not applicable.